Formations and properties PHOTOCATALYTICally active thick films with dioxide titanium - T. M. Pechen (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
For the aims of non-invasive medical spectrophotometry necessary to know the optical properties of biological tissues and fluids. One of the means of definition of the optical characteristics of the layers of the skin is the mathematical modeling of the process of passing of an electromagnetic wave. The Monte-Carlo method is the cornerstone of a technique of modeling. Human skin model used five-layer, the epidermis, the upper part of the dermis, the dermis, the lower part of the dermis, hypodermis. The simulation was performed in the program TracePro, which allows the analysis of the scattered light, the optical analysis of opto-mechanical systems, taking into account absorption, specular reflection and refraction, scattering and diffraction of light aperture.